Robert C. Cook papers - Cook, Robert C. (Robert Carter), 1898-1991.; Cook, Alice Carter, 1868-; Cook, O. F. (Orator Fuller), 1867-1949.; Cook, Robert C. (Robert Carter), 1898-1991.
Correspondence, diaries, writings, research notes, professional files, family and estate papers, genealogical and biographical information on the Carter and Cook families, certificates, awards, photographs, and other papers documenting Cook's career as managing editor and editor of the American Genetic Association's Journal of Heredity, as director and president of the Population Reference Bureau and editor of its Population Bulletin, and as an authority on population policy, eugenics, and the effect of population growth on the environment. Includes material pertaining to his work as a disciplinarian with the Tucson Indian Training School, Escuela, Ariz.; his friendship with geneticist Barbara Stoddard Burks; David Fairchild and Marian Fairchild; the Cosmos Club (Washington, D.C.) relating primarily to the blackballing controversy of the McCarthy-era; Environmental Fund (U.S.); National Association of Science Writers; botany; and rammed earth houses. Includes papers of Cook's parents, Alice Carter Cook and O.F. Cook; drafts of Cook's book, Human Fertility, the Modern Dilemma (1951); and essays by Cook and others on various demographic and ecological topics. Correspondents include J.T. Baldwin, F. Fraser Darling, David Fairchild, George J. Hecht, Clyde E. Keeler, Clarence C. Little, Frank Nicholas Meyer, H.J. Muller, and Frederick Osborn.
Library of Congress Prints and Photographs Division.
Geneticist, demographer, editor, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baldwin, J. T. -- 1910-1974 -- Correspondence; Burks, Barbara Stoddard, -- 1902-1943.; Darling, F. Fraser -- 1903- -- Correspondence; Fairchild, David, -- 1869-1954.; Fairchild, David, -- 1869-1954 -- Correspondence; Fairchild, Marian, -- 1880-1962.; Hecht, George J. -- 1895-1980 -- Correspondence; Keeler, Clyde E. -- 1900-1994 -- Correspondence; Little, Clarence C. -- 1888-1971 -- Correspondence; McCarthy, Joseph, -- 1908-1957.; Meyer, Frank Nicholas -- Correspondence; Muller, H. J. -- 1890-1967 -- Correspondence; Osborn, Frederick, -- 1889-1981 -- Correspondence; Carter family; Cook family; American Genetic Association; Cosmos Club (Washington, D.C.); Environmental Fund (U.S.); National Association of Science Writers; Population Reference Bureau; Tucson Indian Training School; Journal of heredity; Population bulletin; Botany; Conservation of natural resources; Demography; Ecology; Earth houses; Eugenics; Fertility; Genetics; Heredity; Human ecology; Indians of North America -- Education; Population; Population policy; Demographers; Editors; Geneticists